Mobile design for medical care and minor emergencies applying telemedicine - Misael Lazo-Amado; Laberiano Andrade-Arenas (Institute of Advanced Engineering and Science, 2024)
The large number of patients today in hospitals or clinics shows a total collapse in the medical areas, this is reflected by the lack of available specialists and the saturation of appointments to attend patients, taking minutes and hours to get to be attended, that is why it is proposed as an objective to design a mobile application for medical care and minor emergencies applying telemedicine offering the main processes of appointment registration, video calls, medical qualification, first aid, prescription management, and emergency calls. This mobile application is made with the Design Thinking methodology that will allow the team to find the main problems or risks of the patient and find a quick solution based on design. The results give response to the 150 patients showing their satisfaction of the proposed solution, also validation by experts is performed indicating a 97% acceptance and specialist doctors indicate satisfaction, accepting that the system is efficient. In conclusion, the applied objective is shown, finding the main problems and looking for quick solutions showing efficiency and satisfaction by patients, experts, and medical specialists.